ESG performance, auditing quality, and investment efficiency: Empirical evidence from China - Wang, Wenbing; Yu, Yanyan; Li, Xuan (Frontiers in Psychology, 2022)
Dramatic changes in the business environment have created demands for additional information such as management discussions, governance information, and financial statement notes that go beyond the coverage of traditional financial reporting. Reliable and complete integrated reporting information (such as ESG information) that has been independently audited by external auditors can help gain stakeholder trust, reduce transaction costs, and improve investment efficiency. This paper examines the impacts of ESG performance on investment efficiency using a sample of Chinese A-share listed companies from 2011 to 2020. The results show that (a) good ESG performance significantly improved investment efficiency, (b) auditing quality partially mediates the relationship between ESG performance and investment efficiency, and (c) the role of ESG performance is relatively weak in non-SOEs, firms in undeveloped regions, and firms with low accounting information quality. This paper contributes to the literature on ESG performance and provides references for ESG practice and corporate sustainable development in emerging countries.